The Difference in Junior Doctor's Knowledge of Patient Safety Based on Experiences of Operative Stations at Medical Faculty of Universitas Sebelas Maret. Mini Thesis,Faculty of Medicine, Sebelas Maret University, Surakarta - Justinus Kurniabudhi Novarianto; Ari Natalia Probandari; Annang Giri Moelyo (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Medical students are the key of the future of patient safety culture, yet it development still focused on the staff level, administratives, and other medical professionals. The patient safety system is designed for more efficient and easier recording of errors, to prevent and mitigate the risks and errors of medical procedure. Surgical procedure are one of the riskiest medical procedure. The experience in surgical stations might increase the junior doctor's knowledge on patient safety. This research aimed to study the difference in junior doctor's knowledge on patient safety based on the experience in surgical stations. Methods: This research used an analytical observational approach with cross sectional design. The study was conducted in RSUD Dr. Moewardi Surakarta on October 2015. The subject of this research are junior doctors in RSUD Dr. Moewardi Surakarta who met the inclusion and exclusion criterias determined by the researcher. Sampling technique used in this study was the total sampling method. The total sample of the study were 226 junior doctors. Data collected from the questionnaire on knowledge of patient safety filled by the samples, the questionnaire has gone through validation and reliability testing phase. Collected data was then analyzed with independent t-test and multivariate linear regression test. Results: The result of independent t-test showed that there was statistically insignificant relationship between the experience of operative stations and the knowledge on patient safety (p=>0,102). The result of multivariate linear regression test showed that there was difference in the quesionnary score between the junior doctors that have went through operative stations and those who have not, with the decrease of 0,787 points on sample's questionary score with more experience on operative stations, even though it was not statistically significant (p=0,525). Conclusions: The level of knowledge regarding patient safety of junior doctors with more operative station experiences are not higher compared to those with fewer operative station experiences. Keywords: patient safety, junior doctor. clerkship, patient safety education, medical education